ANALISIS KEPUASAN PENGUNJUNG PADA DINAS PERPUSTAKAAN DAN ARSIP DAERAH PROVINSI PAPUA - Karen Meike Mamahit (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2019)
This paper presents the results of a study of the effect of library service satisfaction provided by the Provincial Government of Papua. Destruction services are provided through the Regional Library and Archives Service work unit. The independent variable is the service of human resources, the availability of facilities and infrastructure, and information systems. This study uses survey results and documents. The findings explain, that the three independent variables have a positive and significant effect, but the human resource variable has the most dominant influence compared to the other two variables.